Frequency Independent Phase Shifter - Al-Absi, Munir (2006)
A new simple and low cost frequency independent phase shifter is presented. The design is based on the simple op-amp phase shifter with programmable floating resistor and programmable capacitor. The phase shift can be varied using the programmable resistor. Compensation for the variation in the frequency is achieved using the programmable capacitor. Simulation results are also presented.